Ultrasound Medical Image Representation For Systematic Learning - Rani, V. Mary Kiruba; Dhenakaran, S.S (International Journal of Computer Sciences and Engineering, 2018)
Ultrasound screened image is the output screen of ultrasound device. The nature of ultrasound screened image is noisy. These images are produced by sound waves by scanning inside the body. High - Frequency sound waves in the range 1 MHZ to 15 MHZ transmitted from the probe passed through gel to the body and output is produced. Though the technology is improved by detecting the kind of input image format, Ultrasound medical images have a high impact over natural color images since the pixel values range similar. The objective of the article is differentiating computer generated medical images among the collection of images in a dataset. Most of the research approaches have modeled images by its features and detecting it with several images. However, with advance growth in technology, the image quality is better in dimensional effects and thus visually differentiating the images is a significant task. A systematic filtering group of images is the ultimate aim of the work. A number of computer generated medical image in excess of the dataset and the approach starts compares the given digital image to store medical images in the form of key metrics. The values are used to identify medical images. The proposed method has achieved up to 95% of accuracy in identifying ultrasound medical images.